No increased pain among opioid‐dependent individuals treated with extended‐release naltrexone or buprenorphine‐naloxone: A 3‐month randomized study and 9‐month open‐treatment follow‐up study. Issue 2 (31st January 2019) - Latif, Zill‐e‐Huma; Solli, Kristin K.; Opheim, Arild; Kunoe, Nikolaj; Benth, Jūratė Š.; Krajci, Peter; Sharma‐Haase, Kamni; Tanum, Lars
Abstract : Background and Objectives: It is presently unclear whether extended‐release naltrexone hydrochloride treatment induces pain or aggravates existing pain among individuals with opioid use disorders. We assessed changes in pain among individuals receiving treatment with either extended‐release naltrexone hydrochloride or buprenorphine‐naloxone hydrochloride. Methods: This randomized prospective open‐label clinical study included 143 participants (aged 18–60 years) with opioid dependencies, recruited from outpatient addiction clinics at five urban hospitals in Norway. After in‐patient detoxification from opioids, patients were randomized to 12‐week treatment with either long‐acting naltrexone (380 mg intramuscularly injected every four weeks) or buprenorphine‐naloxone (flexible 4–16 mg sublingual doses daily). This phase was followed by a 9‐month open‐treatment study with the participant's choice of either naltrexone or buprenorphine‐naloxone. Changes in pain were assessed every 4 weeks using the Norwegian Short‐Form of McGill Pain Questionnaire. Results: Throughout the study period, we found no increase in mean sensory pain, affective pain, or present pain intensity on the McGill Pain Questionnaire, in either treatment group, including the subgroups of participants with chronic pain. Participants who switched from buprenorphine‐naloxone to extended‐release naltrexone treatment after week 12 reported no increase in pain intensity during longer‐term treatment. Women experienced significantly more affective pain symptoms than men ( p = .01). Discussion and Conclusions: Among individuals with opioid use disorder, switching from daily opioid use to long‐acting naltrexone did not induce pain, or aggravate mild‐to‐moderate chronic pain. Scientific Significance: In opioid‐dependent individuals, mild‐to‐moderate chronic pain was not influenced by opioid agonist or antagonist treatment. Trial Registration: Clinicaltrials.gov #NCT01717963, first registered: Oct 28, 2012. Protocol version # 3C, June 12th 2012. (Am J Addict 2018;XX:1–9)